Homem e sensibilidade em Ludwig Feuerbach: crítica à teologia cristã e à filosofia especulativa - Melo, Regiany Gomes (2012)
The immanent analysis that we direct about Feuerbach ’s criticism directed to religion and Christian theology and speculative philosophy, shows that the main purpose of these developed criticism is linked to the assertion of Feuerbach’s anthropology and,therefore,to understand of man as rational and also sensitive. Feuerbach articulates his critique of religion and Christian theology from the process of alienation of the generic human essence. Feuerbach search in primary sources of classical Christianity and its supernatural exponents his correlative true, material, the demystification of religious images and theological dogmatism. From then on, Feuerbach shows that the Christian religion is an expression of human feelings, human relations, sensitivity, and therefore it is anthropology. However, sentiment expressed by this religion is inhibited by the theological doctrine in the process of development and dogmatic affirmation of theological and rationality, claiming an ideal of castrated male, asexual, denatured. Likewise the modern speculative philosophy, whose maximum exponent is Hegel, based, as the base of the logical system the assertion of absolute being from the abstraction of man and the sensitivity. To Feuerbach the modern philosophy holds itself in the articulation of concepts whose elements are idealistically founded, based in the reason, in other words, the concepts are extracted from the sensible world of panoramas of reality. Thus, for Feuerbach, the modern speculative philosophy becomes an arbitrary philosophy.Moreover,the Feuerbach ’s philosophy is marked by a growing radicalism that is expressed in the defense of a new philosophy that should begin with the non-philosophy, in other words, with the methodological setback established by the "philosophy of school," namely, the sensible objects. The new philosophy must start from the sensible objects for then getting concrete and immanent foundations in the development of the concepts, validating the proper nature as that which man owes its origin and material resources for its existence. The new philosophy or sensualist philosophy seeks to reconstitute the complete knowledge: reason and sensitivity united in the problematization and understanding of man and the world. The goal of this paper is to specify the conceptual centrality of man and the sensitivity that exists in Feuerbach ’s critical framework and show tha t the criticism aimed at the implementation of emancipation and human consciousness, because, for Feuerbach, the only way man can act an active role in social development in search of the common good. Sensibility.